The Prevent Duty in Education Impact, Enactment and Implications - Busher, Joel; Jerome, Lee (Springer Nature, 2020)
This open access book explores the enactment, impact and implications of the Prevent Duty across a range of educational contexts. In July 2015 the UK became the first country to place a specific legal requirement on those working in education to contribute to efforts to 'prevent people from being drawn into terrorism'. Drawing on extensive research with staff, children and young people, the editors and contributors provide new insight into how this high-profile - and highly contentious - policy has shaped educational practice in Britain today. It will be a valuable resource for researchers, policymakers and others interested in the design, implementation and on-the-ground effects of Prevent or similar programmes internationally that place education at the heart of efforts to prevent or counter violent extremism.